Efficient aqueous hydrogenation of levulinic acid to γ-valerolactone over a highly active and stable ruthenium catalyst. Issue 5 (13th October 2015) - Tan, Jingjing; Cui, Jinglei; Ding, Guoqiang; Deng, Tiansheng; Zhu, Yulei; Li, Yong-wang
Abstract : Efficient aqueous hydrogenation of levulinic acid to γ-valerolactone over a highly active and stable immobilized ruthenium catalyst with a GVL yield of 99.1 mol% at 25 °C. Abstract : Efficient aqueous hydrogenation of levulinic acid over supported catalysts is of fundamental and industrial interest but is highly challenging. For Ru/γ-Al2 O3 catalysts, the primary problems are low activity and stability that arose from the inhomogeneous dispersion of Ru and the unstable nature of γ-Al2 O3 in water. In this work, an integrated strategy was proposed for developing a highly active and stable catalyst for aqueous hydrogenation of LA to GVL. By modification with 3-aminopropyltriethoxysilane (KH550), the abundant surface Al–OH groups of γ-Al2 O3 were transformed into a stable Al–O–Si structure, while ruthenium active centres were bonded to a γ-Al2 O3 surface via coordination with amino ligands of KH550. This modification favours the formation of highly dispersed Ru centres with an electron-rich state, leading to a superior activity at temperatures as low as 25 °C (GVL yield of 99.1%, TOF of 306 h −1 ) and high stability.